Worldwide cohort study of 46, XY differences/disorders of sex development genetic diagnoses: geographic and ethnic differences in variants - Jiali, Chen; Huifang, Peng; Yuqing, Jiang; Xiantao, Zeng; Hongwei, Jiang (Frontiers in Genetics, 2024)
Differences/disorders of sex development (DSDs) in individuals with a 46, XY karyotype are a group of congenital disorders that manifest as male gonadal hypoplasia or abnormalities of the external genitalia. Approximately 50% of patients with 46, XY DSDs cannot obtain a molecular diagnosis. The aims of this paper were to review the most common causative genes and rare genes in patients with 46, XY DSDs, analyze global molecular diagnostic cohorts for the prevalence and geographic distribution of causative genes, and identify the factors affecting cohort detection results. Although the spectrum of genetic variants varies across regions and the severity of the clinical phenotype varies across patients, next-generation sequencing (NGS), the most commonly used detection method, can still reveal genetic variants and aid in diagnosis. A comparison of the detection rates of various sequencing modalities revealed that whole-exome sequencing (WES) facilitates a greater rate of molecular diagnosis of the disease than panel sequencing. Whole-genome sequencing (WGS), third-generation sequencing, and algorithm advancements will contribute to the improvement of detection efficiency. The most commonly mutated genes associated with androgen synthesis and action are AR, SR5A2, and HSD17B3, and the most commonly mutated genes involved in gonadal formation are NR5A1 and MAP3K1. Detection results are affected by differences in enrollment criteria and sequencing technologies.